Aqidah al-salaf wa as'hab al-hadith : aw, al-Risalah fi i'tiqad ahl al-sunnah wa-as'hab al-hadith wa-al-a'mmah - Sabuni, Abi 'Uthman Isma'il ibn 'Abd al-Rahman; al-Jadi'iq, Nasir ibn 'Abd Rahman ibn Muhammad (Riyadh : Dar Alasimah, 1998)
PSZKLL